Recent advances in extracellular vesicles enriched with non-coding RNAs related to cancers - Song Yang; Xi Li (Genes and Diseases, 2018)
As membrane-bound structures that could be shedded by a parental cell, and fuse with others after shedding, and then release its contents, extracellular vesicles (EVs) are considered as an indispensable part of intercellular communication system. The EV contents might be all kinds of bioactive molecules including non-coding RNAs (ncRNAs), a large and complex group of RNAs with various subtypes that function to regulate biological events but classically do not code for proteins. In this review we covered the recently published works that validated the underlying molecular mechanisms regulating EV-associated ncRNAs' biogenesis, signaling, and particularly the systemic bio-effects related mostly to any stage of cancer progression, and the clinical potential of ncRNA-carrying EVs as diagnostic biomarkers and drug-delivery system that is being engineered for better loading and targeting capacity. Our views on the future direction of basic research and applications of EVs containing ncRNAs have also been shared.